REFLECTIVE PRACTICE IN TEACHING: A PATHWAY TO PROFESSIONAL SUSTAINABILITY AND TEACHER WELL-BEING - Usmanova Nilufar Khasan qizi (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The aim of this study is to explore how reflective practice can serve as an effective pedagogical tool to reduce teacher burnout and promote sustainable teaching practices within contemporary educational environments. The research seeks to identify the ways in which self-reflection, peer reflection, and critical analysis of teaching experiences contribute to teachers’ emotional resilience, professional growth, and long-term job satisfaction. It further examines how reflective engagement enhances teachers’ capacity to cope with instructional challenges, adapt to changing classroom dynamics, and maintain motivation in demanding professional contexts. In addition, the study aims to investigate the relationship between reflective practice and teachers’ professional identity development, collaborative learning culture, and instructional effectiveness. Particular attention is given to how structured reflective activities support teachers in recognizing stress factors, developing adaptive coping strategies, and fostering supportive professional communities. Furthermore, the research seeks to design and propose a practical framework that integrates reflective strategies into teacher education programs and continuous professional development initiatives. This framework aims to institutionalize reflective practice as a sustainable professional habit, ensuring long-term teacher well-being, improved teaching quality, and increased retention within the teaching profession.